Study on properties of pre-alloy powder of TiNiHf high temperature shape memory alloy for additive manufacturing by preheating treatment - M.C. Jiang; X.Y. Yang; M.C. Zhang; D.C. Ren; H.F. Nurly; Y. Liu; Y.S. Cai; H.B. Ji; J.F. Lei (Journal of Materials Research and Technology)
In this work, pre-alloyed powder high-temperature shape memory alloy (Ti30Ni50Hf20) for additive manufacturing was preheated at 300–800 °C and thermoscycled at 650 °C to examine the influence of preheating temperature and thermal cycle number on the phase composition and phase transformation behavior. The results showed that the H phase precipitation occurred in the matrix with the rising preheating temperature within 300–600 °C, and the phase transformation temperature of the pre-alloyed powders also increased. When the preheating temperature exceeded 600 °C, the H phase dissolved back into the matrix, and the phase transformation temperature decreased. A total of 50 thermal cycles were conducted on the pre-alloyed powders at 650 °C, and the phase transformation temperature and phase composition remained stable after cycling. It can be concluded that the preheating temperature greatly affected the phase composition and phase transformation behavior of Ti30Ni50Hf20 high-temperature shape memory alloy pre-alloyed powders, while the number of thermal cycles delivered a minor effect.